Genetic Mutations of the Prolactin Gene in Awassi Sheep - Hussein, Hussein Ali; Hassooni, Hadi Awad (American Journal of Botany and Bioengineering, 2025)
The study was conducted on 67 ewes and their offspring at the Khairat Al-Ittihad Sheep and Cattle Breeding Station in Babil Governorate, Iraq, during the period from December 2023 to May 2024. Data were collected from the station's records, including ages, weights, and birth sequences, in addition to laboratory analyses of blood and milk samples. This study aimed to analyze PRL gene mutations in Awassi sheep. DNA was extracted from blood samples using specialized techniques, and the target PRL gene was amplified using polymerase chain reaction (PCR). The results revealed the identification of three mutations in the PRL gene: SNP1: 277 C>T, SNP2: 684 G>T, and SNP3: 737 T>G. The allelic frequencies of the mutations were diverse, with the CC genotype predominating in SNP1, the GT hybrid in SNP2, and the TG hybrid in SNP3.